Tinjauan Koperasi: Sejarah, Aliran, dan Peranannya dalam Ekonomi Global dan Lokal - Dandan Irawan; Adi Puspita Hermawan (J-Coop : Journal of Co-operative, 2025)
Cooperative is an unique economic organizations based on the principles of justice, democracy, and solidarity. This article explores the historical development of cooperatives in various countries, including England, France, Germany, Japan, the United States, etc. highlighting their adaptation to local challenges and needs. From the Industrial Revolution to the modern era, cooperatives have emerged as a response to social and economic inequalities, serving as a balancing force against the adverse effects of capitalism. The article also examines the three main schools of thought on cooperatives, as proposed by Paul Hubert Casselman: Yardstick, Socialist, and Commonwealth, each reflecting the role of cooperatives within different economic systems. Globally, cooperatives play a vital role in strengthening local economies, providing access to financial services, and reducing social disparities. The article further discusses the state of cooperatives in Indonesia and the challenges they face in the modern era. By understanding the history and concepts of cooperatives, this article offers insights into their importance as socio-economic instruments for achieving sustainable community welfare.